Adsorption of manganese in aqueous solution by steel slag - Md Zahar, Mohd Syakirin; Mohd Kusin, Faradiella; Muhammad, Siti Nurjaliah (Elsevier, 2015)
Batch experiments had been conducted to evaluate the ability of steel slag in removing manganese from aqueous solution. Several variables had been setup to evaluate the performance of steel slag in different experimental conditions. The variables include contact time, dosage, pH and initial concentration of manganese. The equilibrium contact time was achieved at 10 hours. 1 g of adsorbent dosage is considered enough to remove heavy metal from aqueous solution. The optimum pH for manganese adsorption onto steel slag was 6. Higher initial concentration leads to the decrease in percentage removal of Mn from solution, but increase in adsorption capacity. The Langmuir isotherm model fits well with data of Mn adsorption onto steel slag compared to Freundlich isotherm model. Steel slag is capable of removing high percentage of Mn from aqueous solution (>95%) in batch experiments, showing potential for real application on-site